Nervilia brevilobata sp. nov. (Orchidaceae) from Taiwan and Hainan. (2nd August 2013) - Hsieh, Szu‐I.; Gale, Stephan W.; Lee, Chi‐Te; Yeh, Chuan‐Rong; Leou, Chong‐Sheng; Yeh, Ching‐Long
Abstract : Nervilia brevilobata C. S. Leou, C. L. Yeh & S. W. Gale sp. nov. (Orchidaceae), discovered in Taiwan and Hainan, is described and illustrated. The new species belongs to the one‐flowered group in Nervilia, but is readily distinguished from other species in the genus by the saccate base of the lip, the truncate‐rounded lobes of the hypochile, and by the relatively short, oblong‐orbicular epichile.